Household transmission of monkeypox - Bonifacio Morales, Nilo (2024)
Monkeypox is a rare disease caused by the monkeypox virus (MPXV). This virus can enter the host through different routes, such as the oropharynx, nasopharynx and intradermal routes, among others. In 2022, an outbreak was reported in which the virus seemed to have mutations that would make it spread more efficiently. We present three cases of monkeypox in a family of eight members. Patient 1, a 32-year-old man, presented with a papule under the left eye, which was hatched manually by his wife. He then developed endophthalmitis associated with fever and headache, in addition to nonpainful vesicular pruritic lesions on the extremities and genitalia. He was eventually clinically diagnosed with monkeypox infection. Patient 2, a 27-year-old woman (wife of patient 1), presented with vesicular and pustular lesions on the chest, extremities and anal area six days after exposure through close contact with patient 1. She subsequently developed myalgia, fever and odynophagia, with a positive molecular test result for MPXV. Patient 3, an 8-year-old boy, presented with odynophagia, tinnitus, fever, cervical lymphadenopathy, and umbilicated papules on the abdomen, left arm, and right buttock seven days after the onset of symptoms in his mother (patient 2). He also tested positive for MPXV on a molecular test. The other family members did not present clinical manifestations despite being in intrafamilial contact with the patients for approximately two weeks, during which they shared common areas and utensils without restrictions.